Hippocampal DNA methylation promotes contextual fear memory persistence by facilitating systems consolidation and cortical engram stabilization - Kupke, Janina; Loizou, Stefanos; Bengtson, C. Peter; Sticht, Carsten; Oliveira, Ana (Biological psychiatry, 2025)
Background - Long-term fear memory storage involves gradual reorganization of supporting brain regions over time, a process termed systems consolidation. Memories initially rely on the hippocampus but gradually shift dependence to the neocortex. Although hippocampal activity drives this transfer, the molecular basis of systems consolidation is largely unknown. DNA methylation changes accompany persistent fear memory formation in the hippocampus and cortex, but its causal role in memory storage and systems consolidation remains unclear. - Methods - We investigated the role of hippocampal DNA methylation in fear memory persistence through multiple approaches. Using recombinant adeno-associated virus (rAAV)-mediated gene transfer, we overexpressed or knocked down a DNA methyltransferase (DNMT3A2) in the dorsal hippocampus of mice and assessed its impact on fear memory duration. Engram tagging and manipulation tools were applied to study cortical fear engram stabilization. Finally, RNA sequencing analysis was used to identify transcriptional changes driven by DNMT3A2 overexpression. - Results - Overexpression of hippocampal DNMT3A2 induced a persistent fear memory, while its knockdown impaired remote memory recall. RNA sequencing revealed that DNMT3A2 overexpression modified the expression of synaptic transmission regulatory genes. Furthermore, genetic engram tagging and manipulation revealed that hippocampal DNA methylation promoted the transfer of the fear memory trace from the hippocampus to the cortex and the stabilization of cortical fear memory traces. - Conclusions - Our findings demonstrate that hippocampal DNA methylation regulates the long-term storage of persistent fear memories by facilitating the transfer of memory traces from the hippocampus to the cortex and cortical stabilization. These results highlight DNA methylation as a key molecular mechanism underlying systems consolidation and long-term fear memory storage.
Gesehen am 18.02.2026